Soils within the steppe and dry steppe zones under anomalous weather conditions in the last tens years - G. S. Bazykina (Бюллетень Почвенного института им. В.В. Докучаева, 2014)
Under consideration is the influence of climate changes (the air temperature rise in the cold 6 months especially in the winter and the increased atmospheric moistening in the warm 6 months) on regimes and properties of soils in dependence on zonal-provincial, geomorphological and lithological conditions as exemplified by the solonetz complex in the semi-desert Pre-Caspian plain and chernozems in central European Russia and southern regions of this country.